Civil Monetary Penalties Resulting From Violations of the Emergency Medical Treatment and Labor Act (EMTALA) Involving Psychiatric Emergencies, 2002 to 2018. (17th April 2019) - Terp, Sophie; Wang, Brandon; Burner, Elizabeth; Connor, Denton; Seabury, Seth A.; Menchine, Michael
Abstract: Objective: The objective was to describe characteristics of civil monetary penalties levied by the Office of the Inspector General (OIG) related to violations of the Emergency Medical Treatment and Labor Act (EMTALA) involving psychiatric emergencies. Methods: Descriptions of EMTALA‐related civil monetary penalty settlements from 2002 to 2018 were obtained from the OIG. Cases related to psychiatric emergencies were identified by inclusion of key words in settlement descriptions. Characteristics of settlements involving EMTALA violations related to psychiatric emergencies including date, amount, and nature of the allegation were described and compared with settlements not involving psychiatric emergencies. Results: Of 230 civil monetary penalty settlements related to EMTALA during the study period, 44 (19%) were related to psychiatric emergencies. The average settlement for psychiatric‐related cases was 85, 488, compared with 32, 004 for non–psychiatric‐related cases (p < 0.001). Five (83%) of the six largest settlements during the study period were related to cases involving psychiatric emergencies. The most commonly cited deficiencies for settlements involving psychiatric patients were failure to provide appropriate medical screening examination (84%) or stabilizing treatment (68%) or arrange appropriate transfer (30%). Failure to provide stabilizing treatment was more common among cases involving psychiatric emergencies (68% vs. 51%, p = 0.041). Among psychiatric‐related settlements, 18 (41%) occurred in CMS Region IV (Southeast) and nine (20%) in Region VII (Central). Conclusions: Nearly one in five civil monetary penalty settlements related to EMTALA violations involved psychiatric emergencies. Settlements related to psychiatric emergencies were more costly and more often associated with failure to stabilize than for nonpsychiatric emergencies. Administrators should evaluate and strengthen policies and procedures related to psychiatric screening examinations, stabilizing care of psychiatric patients boarding in EDs, and transfer policies. Recent large, notable settlements related to EMTALA violations suggest that there is considerable room to improve access to and quality of care for patients with psychiatric emergencies.